Interdisciplinary animal research ethics: challenges, opportunities, and perspectives - Mertz, Marcel; Hetzel, Tatiana; Alex, Karla; Braun, Katharina; Camenzind, Samuel; Dodaro, Rita; Jörgensen, Svea; Linder, Erich; Capas-Peneda, Sara; Reihs, Eva Ingeborg; Tiwari, Vini; Todorović, Zorana; et al. (Animals, 2024)
Can nonhuman animals be used for the benefit of humans in a scientifically and morally justified manner and, if yes, how? Based on our own experiences as scholars from various academic backgrounds, we argue that this question can only be answered as an interdisciplinary and international endeavor, considering insights from research ethics and animal ethics as well as scientific and legal aspects. The aim of this article is to contribute to the foundation of the emerging field of animal research ethics. In doing so, we describe the following seven phases of animal research experiments: ethical, legal and social presumptions (phase 0), planning (phase I), review (phase II), conduct of experiments (phase III), publication/dissemination (phase IV), further exploitation of results (phase V), and evaluation (phase VI). In total, 20 key ethical, legal, and practical challenges that an ethical framework for the use of animals in research needs to address are identified and analyzed. Finally, we characterize the following four meta-challenges and opportunities associated with animal research ethics as a field: (1) moral pluralism, (2) the integration of views and positions outside the laboratory, (3) international plurality of conduct, standards, and legal norms, and (4) interdisciplinary education.